Gender and Climate Resilient Agriculture - Chanana, Nitya; Ma, Stephanie; Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented at the 2021 conference 'Cultivatng Equality: Advancing gender research in agriculture and food systems' organised by the GENDER platform and Wageningen Unversity. The presentation covers the results of a scoping review, of approximately 291 journal as well as grey literature articles related to gender and Climate Resilient Agriculture. Broad trends in terms of time, geographic focus, sector focus, use of intersectionality, and methods of data collection are highlighted. Additionally, a full text review of 154 articles covers different thematic areas within the literature including vulnerability context, climate related impacts, adaptation and gender outcomes. The review results are expected to better inform research efforts as well as project interventions related to climate resilient agriculture.